The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1472-8206.2010.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐dose combinations for cough and common cold in India: an assessment of availability and rationality

Abstract: This study was conducted to determine the number and composition of the various cough and cold formulations available in the Indian market and to study their pharmacological rationale over a period of 7 years. Data for the study was collected from an annual Drug Compendium entitled ‘THE DRUG TODAY’ of the years 2001, 2004, and 2007. Medications were assessed for total number, different formulations, and number of constituents present in each formulation, their pharmacological group and amount of each constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Majority of RP FDCs (86%) in our study were irrational, many of them targeting cough and the common cold, a self-limiting condition that does not require medicine to cure or prevent it. [10] Similar observations have been reported by Roy et al [11] and Desai et al [10] Interestingly, our tool found 14 RP FDCs rational with respect to effi cacy, safety, and compliance. For example, the combination of long acting β 2 agonist with corticosteroid is rational because corticosteroids increase the expression of β 2 receptors by increasing gene transcription and reduces the adverse effects of β2 agonist, whereas β 2 -agonists potentiates the local anti-inflammatory actions of corticosteroids by increasing nuclear localization of glucocorticoid receptors and additive suppression of infl ammatory mediator release.…”
Section: Discussionsupporting
confidence: 89%
“…Majority of RP FDCs (86%) in our study were irrational, many of them targeting cough and the common cold, a self-limiting condition that does not require medicine to cure or prevent it. [10] Similar observations have been reported by Roy et al [11] and Desai et al [10] Interestingly, our tool found 14 RP FDCs rational with respect to effi cacy, safety, and compliance. For example, the combination of long acting β 2 agonist with corticosteroid is rational because corticosteroids increase the expression of β 2 receptors by increasing gene transcription and reduces the adverse effects of β2 agonist, whereas β 2 -agonists potentiates the local anti-inflammatory actions of corticosteroids by increasing nuclear localization of glucocorticoid receptors and additive suppression of infl ammatory mediator release.…”
Section: Discussionsupporting
confidence: 89%
“…The pharmacological rationality of FDCs is established if drugs act by different mechanisms and have supra-additive effect, have similar pharmacokinetics profile, and drugs do not have supraadditive toxicity. 9,10 However, irrational prescribing of FDCs is a major health concern in India as irrational fixed dose combination products can be equally harmful. Many of the FDC available in Indian market lack therapeutic rationale for their use, leading to wasteful expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits have led to an increase in the availability of FDCs for the treatment of cough and cold. Over the past decade, the availability of liquid FDCs for the treatment of cough has increased from 67.9% in 2004 to 71.8% in 2007 [25].…”
Section: Discussionmentioning
confidence: 99%